Odpowiedź:
2.
f(x)= 2x²- 6x + 3
a = 2 , b = - 6 , c = 3
Δ = b² - 4ac = (- 6)² - 4 * 2 * 3 = 36 - 24 = 12
Postać kanoniczna
f(x)= a(x - p)² + q
p = - b/2a = 6/4 = 1 2/4 = 1 1/2
q = - Δ/4a = - 12/8 = - 1 4/8 = - 1 1/2
f(x) = 2(x - 1 1/2)² - 1 1/2
3.
x² - 3x ≤ 0
x(x - 3) ≤ 0
x ≤ 0 ∧ x - 3 ≥ 0 ∨ x ≥ 0 ∧ x - 3 ≤ 0
x ≤ 0 ∧ x ≥ 3 ∨ x ≥ 0 ∧ x ≤ 3
x ≥ 0 ∧ x ≤ 3
x ∈ < 0 , 0 >
∧ - znaczy "i"
∨ - znaczy "lub"
4.
(4x + 12)/x² * (x² + 4x)/(x + 3)
założenie:
x² ≠ 0 ∧ x + 3 ≠ 0
x ≠ 0 ∧ x ≠ - 3
Df: x ∈ R \ {- 3, 0 }
(4x + 12)/x² * (x² + 4x)/(x + 3)=4(x + 3)/x² * x(x + 4)/(x + 3) =
= 4(x + 4)/x